BACKGROUND, PECULIARITIES AND FACTORS OF THE DEVELOPMENT OF TECHNOPARKS IN RUSSIA - Z. K. Baziyan; V. G. Smirnova (Вестник университета)
The article considers the genesis of science, education and business integration forms, as well as reviews the key premises for the emergence and development of technoparks in Russia. The current state of technoparks in Russia, resulting in revealing various factors, affecting the successful functioning of technoparks in a particular region of Russia has been analyzed. It has been concluded, that high research and educational potential of the territories, in which the technoparks are located, remains key condition to the development of the latter